Pharmacological Modulation Of Pain: Comparative Review Of Opioid Vs. Non-Opioid Therapeutic Strategies In Chronic Pain Management (The Review of Diabetic Studies, 2024)
Chronic pain management had remained one of the most challenging areas in clinical medicine, requiring a balance between efficacy and safety. This review explored the comparative pharmacological strategies involving opioid and non-opioid agents in managing chronic pain conditions. Opioid analgesics such as morphine, oxycodone, and fentanyl had historically served as potent agents for moderate-to-severe pain by targeting μ-opioid receptors. However, issues including tolerance, dependence, respiratory depression, and misuse had limited their long-term clinical utility. Non-opioid alternatives, including nonsteroidal anti-inflammatory drugs [NSAIDs], antidepressants, anticonvulsants, and novel agents such as NMDA receptor antagonists and cannabinoid modulators, had emerged as safer and often more sustainable options. These agents acted through diverse mechanisms—modulation of neurotransmitter release, inhibition of prostaglandin synthesis, and regulation of neuropathic signaling—providing multimodal pain control while minimizing opioid-related adverse effects. Despite advances, individualized pain management remained difficult due to variability in patient response, underlying pathology, and comorbidities. Integration of pharmacogenomics, multimodal analgesia, and non-pharmacological interventions was essential to enhance efficacy and safety. Overall, the shift from opioid-centric therapy to balanced, evidence-based multimodal strategies had redefined pain management. Future research should emphasize precision prescribing, opioid-sparing regimens, and ethical prescribing frameworks to optimize chronic pain control while minimizing public health risks.